The poverty business: landlords, illicit practices and reproduction of disadvantaged neighbourhoods in Czechia - Kupka, Petr (Trends in organized crime, 2021)
This paper is guided by the question: How do illicit practices of organized groups contribute to the formation and reproduction of disadvantaged neighbourhoods in Czechia? By asking this question we depart from the dominant understanding of disadvantaged neighbourhoods in the study of organized crime. Instead of seeing them as “breeding grounds of organized crime”, it is explored how regular neighbourhoods can decline as a result of illicit practices carried out by certain organized groups. The context of the paper is the so-called “poverty business”, which refers to the renting of overpriced, substandard housing, financed considerably using housing benefits and thus exploiting the housing need of vulnerable social groups, namely Roma. Using the literature on Roma marginalization and illicit housing practices, an analytical framework that consists of the concepts of speculation, exploitation and liquidation is created and applied to two cases of disadvantaged neighbourhoods: “the Hostel” in Brno and “the Neighbourhood” in Litvínov. In conclusion, the adequacy of the organized crime perspective is critically discussed and the need for further research articulated.